A nano boron carbide / copper composite material and preparation method thereof
By laser excitation of microboro carbide and using copper molten pool convection refinement technology, combined with thermal isostatic pressure treatment, the complex problems of particle distribution and process in the preparation of nanoparticle-reinforced copper-based composite materials are solved, and nanoboro carbide/copper composite is realized The high performance and simplified process of the material improve the comprehensive performance and controllability of the material.
Patent Information
- Application Number
- CN202211536831.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-02
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-12-02
AI Technical Summary
In the prior art, the preparation of nanoparticle reinforced copper-based composite materials has problems such as difficulty in controlling particle size and distribution, complex process and long periods of material comprehensive performance.
The nanoborocarbide particles are further refined through the copper molten pool Marangoni convection to achieve uniform dispersion in the copper matrix. Combined with thermal isostatic densification, nanoborocarbide is prepared /Copper composite material.
The high strength, toughness, high conductivity and high thermal stability of nanoborocarbide/copper composites are achieved, the preparation process is simplified, the cost is reduced, and the controllability and flexibility of the material is improved.
Smart Images

Figure CN115780798B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal composite materials and preparation thereof, and particularly relates to a nano boron carbide / copper composite material and a preparation method thereof. Background Art
[0002] Metallic copper has the advantages of high electrical conductivity / thermal conductivity and low thermal expansion coefficient, and is widely used in aerospace, rail transportation, electronic appliances and other fields. However, the strength and hardness of pure copper itself are low, which makes it difficult to meet the needs of certain special working conditions. Therefore, in practical applications, pure copper materials often need to be subjected to essential strengthening treatment. The strength of copper materials can be effectively improved by grain refinement, but its thermal stability is poor and cannot be mass-produced. Although alloying can improve strength and make up for thermal stability defects, a large amount of added alloying elements will affect electron scattering and seriously reduce the electrical conductivity of the material. Adding second phase particles (such as alumina, molybdenum carbide, etc.) to the copper matrix is an effective strengthening method. Fine second phase particles can effectively hinder dislocation movement, pin grain boundaries and inhibit recrystallization, so that the material obtains high strength and high softening temperature. At the same time, the conductivity theory points out that the second phase composite strengthening will not significantly reduce the electrical conductivity and thermal conductivity of the copper matrix. Therefore, people are paying more and more attention to the research of second phase particle reinforced copper-based composite materials.
[0003] For second-phase particle-reinforced copper-based composite materials, the key to obtaining excellent performance is that the reinforcing phase particles are small and evenly distributed and dispersed. The smaller the dispersed second-phase particles are, the better the strengthening effect on the copper matrix. The nanoscale second phase is an ideal reinforcing phase for reinforcing metals, which can increase the strength of the metal while keeping its toughness and plasticity basically unchanged. However, the process of adding nanoscale particles to the metal liquid is complicated, the control requirements are high, and it is difficult to achieve a uniform distribution of nanoparticles. The most widely used nanoparticle-reinforced copper-based composite material is nano-alumina / copper, which is a process that uses the selective oxidation of aluminum in copper-aluminum alloys under low oxygen conditions to generate second-phase particles. The second-phase particles prepared by this method are evenly distributed, but large-particle alumina inclusions will inevitably be produced during the preparation process and are difficult to remove, affecting the comprehensive performance of the material. In addition, some technical solutions for nanoparticle-reinforced copper-based composite materials are also disclosed in the prior art. The patent document with announcement number CN106011700A discloses a high-strength copper-based composite material toughened with boron carbide-silicon carbide whiskers. The whiskers of the reinforcing phase are relatively large, with a diameter of 300-800nm. The distribution of the reinforcing body is not disclosed, the overall strengthening effect is limited, and the tensile strength is only 453MPa. The patent document with announcement number CN103643075A discloses a nanoparticle-reinforced copper-based composite material and a preparation method thereof. In the copper-based composite material, the size of the nano-reinforced phase molybdenum carbide particles is less than 200nm, the tensile strength is greater than or equal to 480MPa, and the conductivity is greater than or equal to 70% IACS. This patent uses an electron beam physical vapor deposition process, which has high technical requirements for the process and equipment, and is limited to the preparation of thin plates. The patent document with announcement number CN114293051A discloses a method for preparing a high-temperature softening-resistant, high-strength, high-conductivity copper-based composite molded part. The reinforcing phase molybdenum carbide particles are evenly distributed in the copper matrix, with a size of less than 50nm, a softening temperature of 580-950℃, a tensile strength of 476-712MPa, and a conductivity of 82-94IACS%. The patent preparation method involves a complex precursor powder preparation process such as coprecipitation, centrifugation, filtration, drying, and high-temperature reduction, and the toughness, plasticity, and machinability of the material have not been disclosed. It can be seen that the current preparation of nanoparticle-reinforced copper-based composite materials still has problems such as difficulty in controlling particle size and distribution, complex process and long cycle, and the need to further improve the comprehensive performance of the material. Summary of the invention
[0004] In view of the above problems to be solved, the present invention provides a nano boron carbide / copper composite material and a preparation method thereof. The present invention uses laser to excite micron boron carbide to melt, and the melted droplets are further refined and reduced by the Marangoni convection of the copper molten pool, and finally the nano-level boron carbide particles are evenly dispersed in the copper matrix. The prepared nano boron carbide / copper composite material has good composite effect, high toughness, high conductivity and high thermal stability, and has broad application prospects.
[0005] To achieve the above objectives, the present invention can be implemented by the following scheme:
[0006] The present invention provides a method for preparing the nano boron carbide / copper composite material, and the specific preparation method is:
[0007] (1) mixing high-purity copper powder and micron boron carbide powder evenly to form a mixed powder;
[0008] (2) The mixed powder is subjected to additive manufacturing by selective laser melting technology to produce a nano boron carbide / copper composite material;
[0009] (3) Performing hot isostatic pressing densification treatment on the nano boron carbide / copper composite material.
[0010] In the step (1), the mixing is performed by mechanical mixing, wherein the mechanical mixing is a high-speed stirring process, wherein the specific stirring speed is 1000-2000 rpm, the duration is 5-15 minutes, and the process is repeated once; and the high-speed stirring process is protected by an inert atmosphere.
[0011] In the step (1), the high-purity copper powder is spherical and has a particle size of 15-53 μm; the particle size of the micron boron carbide powder is 2-4 μm.
[0012] In the step (1), the volume fraction of the high-purity copper powder is 90-95 vol.%, and the volume fraction of the micron boron carbide powder is 5-10 vol.%.
[0013] In the step (2), the process parameters of the selective laser melting technology are as follows: the laser spot diameter is 60-100 μm, the laser power is 130-200 W, the laser scanning speed is 200-1100 mm / s, the laser scanning spacing is 20-80 μm, and the laser scanning mode is orthogonal strip scanning; preferably, the powder thickness is set to 10-30 μm;
[0014] As an embodiment of the present invention, in step (2), the process parameters of the selective laser melting technology are as follows: for the mixed powder (5 vol.% micron boron carbide + 95 vol.% high purity copper powder), the laser spot diameter is 60 μm, the laser power is 170 W, the laser scanning speed is 300 mm / s, and the laser scanning spacing is 40 μm; for the mixed powder (10 vol.% micron boron carbide + 90 vol.% high purity copper powder), the laser spot diameter is 60 μm, the laser power is 150 W, the laser scanning speed is 1000 mm / s, and the laser scanning spacing is 40 μm.
[0015] The step (2) is carried out under an argon protective atmosphere, with an outlet gas pressure of 3-5 KPa, a powder feeding gas flow rate of 4-5 L / min, and a protective gas flow rate of 40-50 L / min.
[0016] In the step (3), the pressure of the hot isostatic pressing treatment is 50-150 MPa, the temperature is 700-900° C., the holding time is 1-3 hours, and the pressurizing medium is high-purity argon.
[0017] In the step (3), after the hot isostatic pressing treatment is completed, the obtained material is cooled to ambient temperature in an argon atmosphere.
[0018] The present invention provides a nano boron carbide / copper composite material, wherein the volume fraction of nano boron carbide particles is 5-10 vol.%, and the particle size is about 20-70 nm. The performance indicators of the composite material are as follows: tensile strength 712-940 MPa, elongation 12.7-14.7%, electrical conductivity 60-80% IACS, and softening temperature greater than 900°C.
[0019] The key point of the present invention is that by rationally optimizing the laser printing parameters, the laser excites the boron carbide and copper to melt together, and the molten boron carbide droplets are further stirred and dispersed by the strong convection field (Marangoni convection) inside the copper molten pool, and are refined and reduced in size. After solidification, nano-scale boron carbide particles are formed and evenly dispersed in the copper matrix. The strong convection field in the molten pool not only plays a role in stirring and dispersing, but also promotes the full contact between the boron carbide and the copper matrix, improves the interface bonding ability between the two, and thus effectively transfers the load. In addition, rapid heating / cooling (10 7 The process of 300K / s) can effectively avoid the unfavorable diffusion and harmful reaction between the copper matrix and boron carbide. The final generated nano boron carbide particles have a good composite effect with the copper matrix, which can improve the strength, hardness and softening temperature of the copper matrix, and have little effect on electrical conductivity, thermal conductivity and toughness and plasticity.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) Compared with the traditional complex preparation methods of precursor composite powders (ball milling, coprecipitation, adsorption, etc.), the mechanical mixing method used in the present invention is simpler and more effective, and is suitable for large-scale preparation. At the same time, the reinforcement powder is selected from micron-sized boron carbide, which greatly reduces the cost compared to directly using nano-sized boron carbide. Nano-sized boron carbide has a large specific surface area, strong electrostatic interaction between particles, and is easy to agglomerate, making it difficult to mechanically mix it with copper powder evenly; the nano-sized boron carbide particles adsorbed on the surface of the copper powder after mixing increase the roughness of the copper powder particles, seriously affecting the powder spreading quality and forming quality during the printing stage; nano-sized boron carbide has a high laser absorption rate due to its extremely large specific surface area, and is prone to overheating during printing, resulting in melt instability, powder splashing, and pore generation. The use of micron-sized boron carbide particles can well avoid the above-mentioned unfavorable factors.
[0022] (2) The present invention adopts the selective laser melting technology, which has fast forming efficiency and high efficiency, and the final product structure is not restricted and has strong designability. More importantly, the present invention innovatively utilizes the absorption characteristics of boron carbide to laser, and uses laser to excite the melting of micron boron carbide. The melted droplets are further refined and reduced by the Marangoni convection of the copper molten pool, and finally the nano-level boron carbide particles are evenly dispersed in the copper matrix. The dispersed nano boron carbide particles can play a role in load strengthening, grain refinement, dislocation density strengthening and Orowan strengthening, improve the mechanical properties of copper, and have little effect on electrical conductivity, thermal conductivity and toughness and plasticity.
[0023] (3) The present invention introduces boron carbide particles into the copper matrix by adding external reinforcement particles. Compared with the traditional in-situ self-generation (aluminum oxide / copper) method, it has stronger controllability and flexibility, and the upper limit of the particle addition amount is greatly improved, which makes it possible to obtain a copper-based composite material with higher strength.
[0024] (4) The nano boron carbide / copper composite material provided by the present invention has excellent tensile strength (712-940 MPa) and tensile plasticity (elongation of 12.7-14.7%). In addition, the composite material has excellent electrical conductivity (60-80% IACS), and its "strength-conductivity" comprehensive performance is higher than that of most copper alloys and is comparable to the best copper-silver alloy. It has excellent thermal stability, with a softening temperature greater than 900°C, which is better than copper-niobium alloy.
[0025] (5) In addition, the present invention can further optimize the parameters of the selective laser melting process, and by optimizing the process parameters to adjust the laser energy density, the controllable and customized forming of nano-boron carbide / copper composite materials with different volume fractions can be achieved. For 5 vol.% nano-boron carbide / copper composite materials, the optimal process parameters of the selective laser melting can be set as follows: the laser spot diameter is 60 μm, the laser power is 170 W, the laser scanning speed is 300 mm / s, the laser scanning spacing is 40 μm, the laser scanning mode is orthogonal strip scanning, and the powder thickness is set to 20 μm. Under this process, micron-sized boron carbide can be melted and dispersed into uniform and fine nano-boron carbide particles, which are evenly distributed and well combined with the copper matrix, and the density reaches 97.9%. For 10vol.% nano boron carbide / copper composite materials, the optimal process parameters of selective laser melting can be set as follows: the laser spot diameter is 60μm, the laser power is 150W, the laser scanning speed is 1000mm / s, the laser scanning spacing is 40μm, the laser scanning mode is orthogonal strip scanning, and the powder thickness is set to 20μm. Under this process, micron-sized boron carbide can be melted and dispersed into uniform and fine nano boron carbide particles. The particle size and morphology are consistent with those of the 5vol.% sample, and the distribution is uniform and well combined with the copper matrix, with a density of 97.4%. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0027] Figure 1 The surface morphologies of the micron boron carbide powder and spherical copper powder used in Example 1 of the present invention; (a) is a morphology of boron carbide powder with a particle size of 2-4 μm; (b) is a morphology of spherical copper powder with a particle size of 15-53 μm;
[0028] Figure 2 Surface morphology of the 10 vol.% nano-boron carbide / copper composite material and particle size statistics of its nano-boron carbide particles in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0030] The nano boron carbide / copper composite material and the preparation method thereof described in the present invention have the following specific preparation steps:
[0031] (1) high-purity copper powder and micron boron carbide powder are uniformly mixed by mechanical mixing;
[0032] (2) The mixed powder is subjected to additive manufacturing by selective laser melting technology to produce a nano boron carbide / copper composite material;
[0033] (3) Performing hot isostatic pressing densification treatment on the nano boron carbide / copper composite material.
[0034] Example 1
[0035] This example prepares a 10 vol.% nano boron carbide / copper composite material, and the preparation method is as follows:
[0036] 31.5 g of boron carbide powder (such as Figure 1 (a)) and 1 kg of spherical copper powder with a particle size of 15-53 μm (as shown in Figure 1 (b) is placed in a stirring tank and mechanically mixed under an argon atmosphere. The stirring speed is 1600 rpm and the stirring time is 10 min. This is repeated once to obtain a uniformly mixed boron carbide / copper composite powder. The composite powder is used as the raw material, and the selective laser melting process is used to carry out additive manufacturing of nano-boron carbide / copper composite materials. The selective laser melting process parameters are as follows: the laser spot diameter is 60 μm, the laser power is 150 W, the laser scanning speed is 1000 mm / s, the laser scanning spacing is 40 μm, the laser scanning method is orthogonal strip scanning, and the powder thickness is set to 20 μm. The additive manufacturing process is carried out under an argon atmosphere with an outlet pressure of 5 KPa. The nano-boron carbide / copper composite material obtained by additive manufacturing is placed in a hot isostatic pressing furnace, and the pressure is maintained at 90 MPa for 1 hour under an argon medium at 700 ° C. It is cooled to room temperature with the furnace under an argon environment to obtain a further densified 10 vol.% nano-boron carbide / copper composite material, as shown in FIG. Figure 2 As shown, nano-boron carbide is uniformly dispersed in the copper matrix, and the particle size is about 50nm.
[0037] In this embodiment, the obtained nano boron carbide / copper composite material has a tensile strength of 940 MPa, an elongation of 12.7%, a conductivity of 60% IACS, and a softening temperature greater than 900°C.
[0038] Example 2
[0039] This example prepares a 5 vol.% nano boron carbide / copper composite material, and the preparation method is as follows:
[0040] 14.9g of boron carbide powder with a particle size of 2-4μm and 1kg of spherical copper powder with a particle size of 15-53μm were placed in a stirring tank and mechanically mixed under an argon atmosphere. The stirring speed was 1600rpm and the stirring time was 10min. This was repeated once to obtain a uniformly mixed boron carbide / copper composite powder. The composite powder was used as the raw material and the additive manufacturing of nano-boron carbide / copper composite materials was carried out by selective laser melting. The process parameters of the selective laser melting were as follows: the laser spot diameter was 60μm, the laser power was 170W, the laser scanning speed was 300mm / s, the laser scanning spacing was 40μm, the laser scanning mode was orthogonal strip scanning, and the powder thickness was set to 20μm. The additive manufacturing process was carried out under an argon atmosphere with an outlet pressure of 5KPa. The nano boron carbide / copper composite material obtained by additive manufacturing was placed in a hot isostatic pressing furnace, maintained at 90 MPa for 1 hour under 700°C argon medium, and cooled to room temperature in the argon environment to obtain a further densified 5 vol.% nano boron carbide / copper composite material.
[0041] In this embodiment, the obtained nano boron carbide / copper composite material has a tensile strength of 712 MPa, an elongation of 14.7%, a conductivity of 75% IACS, and a softening temperature greater than 900°C.
[0042] Comparative Example 1
[0043] The difference between Comparative Example 1 and Example 1 is that the boron carbide powder with a particle size of 2-4 μm is replaced by boron carbide powder with a particle size of 50 nm.
[0044] Comparative Example 2
[0045] The difference between Comparative Example 2 and Example 2 is that the boron carbide powder with a particle size of 2-4 μm is replaced by boron carbide powder with a particle size of 50 nm.
[0046] Comparative Example 3
[0047] The preparation methods of the nano boron carbide / copper composite material in Comparative Example 3 and Example 1 are basically the same, except that in Comparative Example 3, the laser power is 120W.
[0048] Comparative Example 4
[0049] The preparation methods of the nano boron carbide / copper composite material in Comparative Example 4 and Example 1 are basically the same, except that in Comparative Example 3, the laser power is 210W.
[0050] Comparative Example 5
[0051] The preparation methods of the nano boron carbide / copper composite material in Comparative Example 5 and Example 1 are basically the same, except that in Comparative Example 5, the laser scanning speed is 100 mm / s.
[0052] Comparative Example 6
[0053] The preparation methods of the nano boron carbide / copper composite material in Comparative Example 6 and Example 1 are basically the same, except that in Comparative Example 6, the laser scanning speed is 1200 mm / s.
[0054] Comparative Examples 7-10
[0055] The preparation methods of the nano boron carbide / copper composite materials in Comparative Examples 7-10 are basically the same as those in Example 2, with the only difference being that in Comparative Example 7, the laser power is 120 W; in Comparative Example 8, the laser power is 210 W; in Comparative Example 9, the laser scanning speed is 100 mm / s; and in Comparative Example 10, the laser scanning speed is 1200 mm / s.
[0056] Performance Testing
[0057] The performance test of the composite materials prepared in each embodiment and comparative example is carried out
[0058] The performance test conditions are as follows:
[0059] The detection methods of tensile strength and elongation refer to GB / T228.1-2010. The electrical conductivity is tested by an eddy current measuring instrument, referring to GB / T351-2019. Through the performance comparison of the experimental examples and the comparative examples, it can be found that, as shown in Table 1 and Table 2, the nano boron carbide / copper composite material in the embodiment of the present invention has excellent toughness, high conductivity and high thermal stability.
[0060] Table 1
[0061] Tensile strength(MPa) Elongation(%) Electrical conductivity (%IACS) Softening temperature(℃) Example 1 940 12.7 60 >900 Comparative Example 1 676 1.2 43 750 Comparative Example 3 817 1.3 52 700 Comparative Example 4 840 7.8 49 750 Comparative Example 5 883 5.7 51 850 Comparative Example 6 791 10.2 62 800
[0062] Table 2
[0063] Tensile strength(MPa) Elongation(%) Electrical conductivity (%IACS) Softening temperature(℃) Example 2 712 14.7 75 >900 Comparative Example 2 533 3.5 62 600 Comparative Example 7 642 7.7 70 750 Comparative Example 8 677 9.4 69 800 Comparative Example 9 653 8.8 71 850 Comparative Example 10 620 12.5 76 800
[0064] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a nano boron carbide / copper composite material, It is characterized in that The method for preparing the nano boron carbide / copper composite material comprises the following steps: (1) High-purity copper powder and micron boron carbide powder are mixed evenly to form a mixed powder; the high-purity copper powder is spherical and has a particle size of 15-53 μm; the particle size of the micron boron carbide powder is 2-4 μm; (2) The mixed powder is subjected to additive manufacturing by selective laser melting technology to produce a nano boron carbide / copper composite material; (3) performing hot isostatic pressing densification treatment on the nano boron carbide / copper composite material; In the step (1), in the mixed powder, the volume fraction of high-purity copper powder is 90-95 vol.%, and the volume fraction of micron boron carbide powder is 5-10 vol.%; The process parameters of the selective laser melting technology are as follows: the laser spot diameter is 60-100 μm, the laser power is 130-200 W, the laser scanning speed is 200-1100 mm / s, the laser scanning spacing is 20-80 μm, and the laser scanning mode is orthogonal strip scanning; the powder thickness is set to 10-30 μm.
2. The preparation method according to claim 1, It is characterized in that In the step (1), the mixing is performed by mechanical mixing, wherein the mechanical mixing is a high-speed stirring process with a stirring speed of 1000-2000 rpm and a duration of 5-15 min, and the high-speed stirring process is protected by an inert atmosphere.
3. The preparation method according to claim 1, It is characterized in that The step (2) is carried out under an argon protective atmosphere, with an outlet gas pressure of 3-5 KPa, a powder feeding gas flow rate of 4-5 L / min, and a protective gas flow rate of 40-50 L / min.
4. The preparation method according to claim 1, It is characterized in that In the step (3), the pressure of the hot isostatic pressing treatment is 50-150 MPa, the temperature is 700-900° C., the holding time is 1-3 h, and the pressurizing medium is high-purity argon.
5. The preparation method according to claim 1, It is characterized in that In the step (3), after the hot isostatic pressing treatment is completed, the obtained material is cooled to ambient temperature in an argon atmosphere.
6. A nano boron carbide / copper composite material prepared by the preparation method according to any one of claims 1 to 5.
7. The nano boron carbide / copper composite material according to claim 6, It is characterized in that In the nano-boron carbide / copper composite material, the volume fraction of nano-boron carbide particles is 5-10 vol.%, and the particle size of the nano-boron carbide particles is 20-70 nm.
